ANALISIS KANDUNGAN KADMIUM (Cd) DAN TIMBAL (Pb) PADA AIR SUMUR GALI PENDUDUK DI SEKITAR INDUSTRI DAUR ULANG AKI DAN GANGGUAN KESEHATAN PADA MASYARAKAT DESA BANDAR KHALIPAH KABUPATEN DELI SERDANG TAHUN 2013 - Ahmad Fandi Irfandi; taufik ashar; indra chahaya (Lingkungan dan Kesehatan Kerja, 2014)
Battery recycling industry is one effective way to avoid the junk pile B3. However, the processing is not oriented environment it becomes a threat to the environment and the health of the surrounding population. The objective of this study to know the content of Cadmium and Plumbum in the public dig well water around the battery recycling industry and health problems in public. Kind of descriptive study that observatifs sanitary dig well, the content of Cadmium and Plumbum in water dig well, and health problems in public living around the battery recycling indusrtry. Sample wells were taken 10 point 50 meters from the industry, and people who live im the Dusun III. The research found sanitary well contamination risk (100%), standard water containing Cd eligible (100%) and Pb (90%). Drinking water standards are not eligible Cd (20%) and Pb (100%). Helath problems in public include itching of the skin (25%), dry scaly skin disorders (21,7%), itchy and scaly skin disorders (15,2%), nausea (6,5%), death taste (21,7%), black feaces (42,4%), bone pain and difficulty moving (1,1%), back pain (2,2%) and increased blood pressure (7,6%). Suggested the role of government in an effort to control the industry and increasing public knowledge about well water contamination from battery recycling industry and sanitary dig well through training, extension and restoration, so avoid health problems. Keywords: Sanitary Dig Well, Cadmium and Plumbum, Health Problems